Molecular characterization of Bipolaris spp. using universal rice primer (URP) markers - SANGEETA GUPTA, SAPNA SHARMA*, B.M. BASHYAL; RASHMI AGGARWAL, SAGAR BANERJEE, RAJSHREE POSWAL, (Indian Phytopathology, 2014)
Bipolaris species are phytopathogenic to many cereal crops. Genetic variability in different isolates of B. sorokiniana and other species of Bipolaris infecting cereals has been studied using URP (universal rice primers) markers. Fourteen isolates of B. sorokiniana collected from different geographical locations of India and one each of B. maydis, B. oryzae, B. tetramera and B. spicifera were taken for the study. Out of 12 URP markers used in the study, 7 markers effectively produced polymorphic bands in all the isolates. The analysis of entire fingerprint profile using unweighted pair group method with arithmetic averages (UPGMA) differentiated B. tetramera, B. spicifera, B. maydis and B. sorokiniana. Twelve isolates of B. sorokiniana out of 14 taken for the study, showed more than 70% similarity. Isolates BS-60 and BS-120 showed more than 90% similarity. One of the markers, URP 2F amplified a band of 700bp which was present in all the isolates of B. sorokiniana which could be further explored to develop species specific diagnostic marker.